Skin sample preparation by collagenase digestion for diclofenac quantification using LC–MS/MS after topical application. (June 2016) - Nirogi, Ramakrishna; Padala, Naga Surya Prakash; Boggavarapu, Rajesh Kumar; Kalaikadhiban, Ilayaraja; Ajjala, Devender Reddy; Bhyrapuneni, Gopinadh; Muddana, Nageswara Rao
Background: Skin is the target site to evaluate the pharmacokinetic parameters of topical applications. Sample preparation is one of the influential steps in the bioanalysis of drugs in the skin. Evaluation of dermatopharmacokinetics at preclinical stage is challenging due to lack of proper sample preparation method. There is a need for an efficient sample preparation procedure for quantification of drugs in the skin using LC–MS/MS.Results: The skin samples treated with collagenase followed by homogenization using a bead beater represents a best-fit method resulting in uniform homogenate for reproducible results.Conclusion: A new approach involving enzymatic treatment and mechanical homogenization techniques were evaluated for efficient sample preparation of skin samples in the bioanalysis.